ANALISIS WACANA KRITIS PERSPEKTIF KALIMAT DALAM TALK SHOW MATA NAJWA TENTANG UU OMNIBUS LAW CIPTA KERJA DI TRANS7 - Deri Wan Minto (Jurnal Semantik, 2022)
The background of this research seen from the mass media, especially television, has become a necessity in addressing the perspectives that occur in society. Television can determine the ideology, interests and points of view to influence others. This study aims to describe Najwa Shihab's partisanship, social cognition, and context in the Mata Najwa event at Trans7 regarding the Omnibus Law: Job Creation in Trans7 Model Teun A. Van Dijk. This type of research is qualitative with a Critical Discourse Analysis (AWK) system approach. The data is in the form of speeches from the presenters in the Mata Najwa program with the concept of taking part in the host, whether to the "Pro Team" (to the government), whether to the "contra team" (to non-government) or not taking sides with both (idependent). Results Based on research and discussion, the number of sentences found in the interactive dialogue “kubu” Pro is 35 sentences. Next, the counter “stronghold” reveals 41 sentences. Based on this research, it is clear that in the program hosted by Najwa Shibab, the sentence structure used has an ideology and characteristics that are impartial, independent, and open. This means that based on the sentence issued by the speaker (the presenter) it is below 50%. This means that the media does not take sides with the government, the counter team, or others. This event purely displays polemics and events that occur in society. Meanwhile, the context of the birth of this event cannot be separated from the polemic of the Job Creation Law which has attracted public attention.